Prophylactic P-selectin inhibition with PSI-421 promotes resolution of venous thrombosis without anticoagulation - Meier, Thomas R.; Myers, Daniel D., Jr; Wrobleski, Shirley K.; Zajkowski, Paul J.; Hawley, Angela E.; Bedard, Patricia W.; Ballard, Nicole E.; Londy, Frank J.; Kaila, Neelu; Vlasuk, George P.; Schaub, Robert G.; Wakefield, Thomas W. (Thrombosis and Haemostasis, 2008)
P-selectin inhibition has been evaluated as a therapeutic for prevention and treatment of venous thrombosis. In this study, a novel oral small-molecule inhibitor of P-selectin, PSI-421, was evaluated in a baboon model of stasis induced deep vein thrombosis (DVT). Experimental groups included i) primates receiving a single oral dose of 1 mg/kg PSI-421 two days prior and continued six days after thrombosis (n=3); ii) primates receiving a single daily subcutaneous dose of 0.57 mg/kg enoxaparin sodium two days prior and continued six days post thrombosis (n=3); and iii) primates receiving no treatment (n=3).PSI-421 treated primates had greater percent vein reopening and less vein wall inflammation than the enoxaparin and controls at day 6. Microparticle tissue factor activity (MPTFA) was significantly lower in the animals receiving PSI-421 immediately after thrombosis (T+6 hours day 0) suggesting lower potential for thrombogenesis in these animals. PSI-421 also reduced soluble P-selectin levels versus controls at T+6 hours day 0, day 2 and 6. Experimental animals in any group showed no adverse effects on coagulation. This study is the first to demonstrate a reduction in MPTFA associated with vein reopening and reduced vein inflammation due to oral P-selectin inhibition in a baboon model of DVT.
Keywords: Venous thrombosis; small-molecule inhibitor of P-selectin; P-selectin; veins; microparticle tissue-factor activity